Types and abundance of periphyton in the glass substrate placed in the Salo River, Salo District, Kampar Regency - Santo Rio Pakpahan; Madju Siagian; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Periphyton it is aquatic microorganisms that are attached in any submerged substrate. This research aims to understand the type and periphyton abundance on glass substrates that were immersed in the Salo River. The research was conducted in August – September 2015. There were 3 stations, namely. Station 1, Station 2 and Station 3. Water quality measured were transparency, temperatur, dissolved oxygen, current velocity, carbon dioxide and pH. Periphyton were then identified. Results shown that there were 33 species and they were included in 5 classes. Bacillariophyceae (22 species), Cyanophyceae (3 species), Chlorophyceae (4 species), Dynophyceae (1 species), and Xanthophyceae (3 species). The abundance of periphyton was 5,460 cell/cm2 – 61,941 cell/cm2. The highest abundance was found in the Station 3 (61,941 cell/cm2) and the lowest was found in the Station 1 (5,460 cell/cm2). Based on data obtained, it can be concluded that the water in the Salo River is categorized as oligotrophic to mesotrophic.Keywords: Salo River, Periphyton, Glass Substrate, Type and Abundance